2021
DOI: 10.3389/fmars.2020.578601
|View full text |Cite
|
Sign up to set email alerts
|

Status and Exploitation of 74 Un-Assessed Demersal Fish and Invertebrate Stocks in the Aegean Sea (Greece) Using Abundance and Resilience

Abstract: Stocks with low market value are rarely included in stock assessments because their catch records are generally lacking, thus adding to the already large number of un-assessed fisheries at a global scale. T his deficiency is more evident in the Mediterranean Sea where stock assessments are relatively fewer. A new method (AMSY) has been recently developed to assess stocks for which only abundance trends from scientific surveys are available. The AMSY method was used in the Aegean Sea to assess the status of 74 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…The assessments undertaken of these cephalopod species available in the Mediterranean showed very diverse stock statuses (Table 4). The critical state of Eledone found in the Strait of Sicily was similar to that reported for its stocks in the Aegean (Tsikliras et al, 2021), Ligurian, and Tyrrhenian Seas (Abella et al, 2010;Giordano et al, 2010;Froese et al, 2018). On the other hand, Agnesi et al (1998) reported a healthy stock status of E. cirrhosa in the Tyrrhenian Sea and Orsi Relini et al (2006) for the Ligurian Sea.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The assessments undertaken of these cephalopod species available in the Mediterranean showed very diverse stock statuses (Table 4). The critical state of Eledone found in the Strait of Sicily was similar to that reported for its stocks in the Aegean (Tsikliras et al, 2021), Ligurian, and Tyrrhenian Seas (Abella et al, 2010;Giordano et al, 2010;Froese et al, 2018). On the other hand, Agnesi et al (1998) reported a healthy stock status of E. cirrhosa in the Tyrrhenian Sea and Orsi Relini et al (2006) for the Ligurian Sea.…”
Section: Discussionsupporting
confidence: 80%
“…Conversely, in other Mediterranean areas, its status ranged from overfishing in the Gulf of Lions (Froese et al, 2018) to severely depleted in the Levantine Sea (Demirel et al, 2020), or critical in the Balearic Islands (Quetglas et al, 2015) and in the Ionian/Adriatic Sea (Froese et al, 2018). As for ommastrephids, the healthy state of Todill found in the Strait of Sicily was similar to that reported for its stocks in the Aegean (Tsikliras et al, 2021) and the Adriatic Seas (Froese et al, 2020). Conversely, Froese et al (2018) found that the state of the ommastrephid squids varied from "overfished" in the Ionian/Aegean Sea and Sardinia to "critical" in the Adriatic Sea.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Lessepsian migrations may represent the 'most important biogeographic phenomenon witnessed in the contemporary oceans' (Por 1978), and also present ongoing opportunities to better understand general biological processes such as species interactions, physiological and ecological adaptations, and evolutionary processes (Ruiz et al 2000;Bernardi et al 2010). The Eastern Mediterranean is oligotrophic (Longhurst 2010), which limits the productivity of the subregion, which also suffers from severe overfishing (Demirel et al 2020;Tsikliras et al 2021). Because of the 'fishing down marine food webs' phenomenon (Pauly et al 1998), which also occurs in the Mediterranean, including its eastern basin (Stergiou 2005;Keskin and Pauly 2018), high-trophic level, large fish (such as sharks) are now rare, leaving room for new non-indigenous top-level predators to establish themselves.…”
Section: Introductionmentioning
confidence: 99%
“…At present, very few species have been formally assessed using the AMSY model, and, based on our knowledge, the present study was the first application on a pelagic stock based on acoustic data. Instead, different examples of demersal stocks are presented in literature: Tsikliras et al (2021) developed an AMSY model for 74 species never assessed in the Aegean Sea, Falsone et al (2021) built AMSY and CMSY models for the Lepidopus caudatus in the Strait of Sicily. The limited diffusion of this model is also due to the fact that it was developed only recently.…”
Section: Discussionmentioning
confidence: 99%